α(1B) adrenergic receptors in gonadotrophin-releasing hormone neurones: relation to Transport-P - Al-Damluji, S (2001)
1. Peptidergic neurones accumulate amines via an unusual uptake process, designated Transport-P. [(3)H]-prazosin binds to α(1) adrenoceptors on these cells and is displaceable by unlabelled prazosin in concentrations up to 10(−7) M. However, at greater concentrations of prazosin, there is a paradoxical accumulation of [(3)H]-prazosin which we have attributed to Transport-P. Uptake of prazosin via Transport-P is detectable at 10(−10) M prazosin concentration, is linear up to 10(−7) M and at greater concentrations becomes non-linear. In contrast, in noradrenergic neurones, noradrenaline uptake is linear and saturates above 10(−7) M. In noradrenergic neurones and in non-neuronal cells, there is no uptake of prazosin in concentrations up to 10(−6) M, suggesting that Transport-P is a specialised function of peptidergic neurones. 2. Using a mouse peptidergic (gonadotrophin-releasing hormone, GnRH) neuronal cell line which possesses Transport-P, we have studied the interaction of α(1) adrenoceptors with Transport-P. Polymerase chain reactions and DNA sequencing of the products demonstrated that only the α(1B) sub-type of adrenoceptors is present in GnRH cells. 3. In COS cells transfected with α(1b) adrenoceptor cDNA and in DDT(1) MF-2 cells which express native α(1B) adrenoceptors, [(3)H]-prazosin was displaced by unlabelled prazosin in a normal equilibrium process, with no prazosin paradox in concentrations up to 10(−6) M. In DDT(1) MF-2 cells, [(3)H]-prazosin was displaced likewise by a series of α(1) adrenergic agonists, none of which increased the binding of [(3)H]-prazosin. Hence, the prazosin paradox is not due to some function of α(1) adrenoceptors, such as internalization of ligand-receptor complexes. 4. In neurones which possess Transport-P, transfection with α(1b) adrenoceptor cDNA resulted in over-expression of α(1B) adrenoceptors, but the prazosin paradox was unaltered. Thus, α(1) adrenoceptors and Transport-P mediate distinct functions in peptidergic neurones.